PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN PADA PT. PLN (PERSERO) ULP AIR MOLEK - Nuraliza "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at PT. PLN (Persero) for the Air Molek area on Jl. ST. Ibrahim, Candirejo, Pasir Turtle, Indarigi Hulu Regency, Riau. The problem in this study is that employee loyalty at PT PLN (Persero) ULP Air Molek is still relatively low, which can be seen from some employees who are less than optimal at work and indiscipline in carrying out their duties and applicable rules. The purpose of this study was to determine the effect of incentives and work motivation on employee loyalty at PT PLN (Persero) ULP Air Molek.In this study, the method used is descriptive and quantitative analysis using the SPSS program. This population is the employees of the Hotel Resty Menara Pekanbaru totaling 50 people. Samples were taken based on the census method or saturated sample, that is, the entire population was used as a sample. Therefore, the sample used in this study was 50 people. Methods of data collection using questionnaires and free interviews. Hypothesis testing using linear analysis methods, simple linear analysis and multiple linear analysis.The research conducted shows the results that for the t-test with the variable giving incentives and work motivation partially significant effect on employee loyalty. And for the results of the F test, it shows that the simultaneous provision of incentives and work motivation has a significant effect on employee loyalty at PT PLN (Persero) ULP Air Molek with an R Square value of 0.448. This shows that the provision of incentives and work motivation has an influence of 44.8% on employee loyalty in the very good category, while the remaining 55.2% is influenced by other variables not examined in this study.Keywords: Giving Incentives, Work Motivation, Loyalty